(untitled) (Costa Rican Journal of Guidance & Counseling, 2024)
This essay proposes that films can be examined through the lens of transactional analysis (TA), even if they were not originally conceived from this perspective. It suggests that with the application of TA analysis, movies can serve as a supportive resource in the professional practice of Guidance Counseling. The aim is to highlight how the film "The Little Prince" can be analyzed using TA premises to enhance the use of such materials in interventions within the field of Guidance Counseling. Utilizing the foundational principles of TA, as proposed by Eric Berne, including conceptualizations such as structural and functional analysis of personality, transactions, psychological games, and life scripts. In concludes that TA allows the analysis of human beings in various contexts, enabling Guidance Counseling professionals to engage in different processes of personal development, such as self-awareness. Furthermore, it determines that cinematic materials have the potential to be analyzed through TA. The analysis of a movie such as "The Little Prince" can reveal a series of TA premises, providing Guidance Counselors with opportunities to use their creativity in constructing diverse work processes aligned with the principles of this discipline.